Factors That Influence and Moderate Smartphone Addiction in Children - Fauziati, Choirunnisak (Proceeding International Symposium on Global Education, Psychology, and Cultural Synergy, 2025)
Smartphone Addiction among children has become a complex and multidimensional phenomenon. Indonesia, as the fourth-largest smartphone user globally, faces significant challenges in addressing this issue. This study aims to identify factors influencing and moderating Smartphone Addiction among children. A literature review was conducted using national and international indexed databases from 2014 to 2024. The findings reveal nine primary factors influencing Smartphone Addiction: (1) duration and intensity of use, (2) smartphone ownership, (3) negative parenting styles, (4) demographic factors, (5) low physical activity, (6) usage motivation, (7) social media usage, (8) technological design, and (9) mental health. Additionally, five factors were identified as moderating these relationships: (1) parental roles and mediation, (2) positive parenting styles, (3) core self-evaluation, (4) connectedness to nature, and (5) gender. This study recommends a collaborative approach involving parents, educators, and policymakers to mitigate the risks of Smartphone Addiction through positive parenting, digital literacy, and smartphone usage restrictions to support children’s mental and emotional development in the digital era. It is anticipated that this study will serve as a foundation for developing strategies to prevent Smartphone Addiction among children in Indonesia.